Addressing concerns over the fate of DNA derived from genetically modified food in the human body: A review. (February 2019) - Nawaz, Muhammad Amjad; Mesnage, Robin; Tsatsakis, Aristides M.; Golokhvast, Kirill S.; Yang, Seung Hwan; Antoniou, Michael N.; Chung, Gyuhwa
Abstract: Global commercialization of GM food and feed has stimulated much debate over the fate of GM food-derived DNA in the body of the consumer and as to whether it poses any health risks. We reviewed the fate of DNA derived from GM food in the human body. During mechanical/chemical processing, integrity of DNA is compromised. Food-DNA can survive harsh processing and digestive conditions with fragments up to a few hundred bp detectable in the gastrointestinal tract. Compelling evidence supported the presence of food (also GM food) derived DNA in the blood and tissues of human/animal. There is limited evidence of food-born DNA integrating into the genome of the consumer and of horizontal transfer of GM crop DNA into gut-bacteria. We find no evidence that transgenes in GM crop-derived foods have a greater propensity for uptake and integration than the host DNA of the plant-food. We found no evidence of plant-food DNA function/expression following transfer to either the gut-bacteria or somatic cells. Strong evidence suggested that plant-food-miRNAs can survive digestion, enter the body and affect gene expression patterns. We envisage that this multi-dimensional review will address questions regarding the fate of GM food-derived DNA and gene-regulatory-RNA in the human body. Highlights: Mechanical and chemical processing, prior to entering digestive system, compromises DNA integrity. DNA fragments up to a few hundred base pairs can survive and reach in blood and tissues of human and animal consumers. There is limited evidence that dietary DNA can integrate into the genome of somatic cells or gut bacteria. There is no evidence that dietary DNA integrated into somatic cells of consumers and gut bacteria has gene expression. Food miRNAs can survive digestion, enter the consumer's body and may affect their gene expression in different organs.